Determinants of quality services provision of local government: evidence from Bangladesh - Ashraf, Musfiqa; Moniruzzaman, Md.; Quddus, S. M. Abdul (Macrothink Institute, 2018)
The present study aimed at exploring the determinants of perceived quality services of Dhaka City Corporation (DCC) provided towards the slum dwellers. For the purpose of the study, data were collected from the respondents with a structured questionnaire survey using stratified random sampling. Collected data were analyzed using partial least squares (PLS) with the support of the software Smart PLS 2.0 M3. The statistical findings of this study reveal that tangibility, responsiveness, reliability, empathy dimensions and logistic supports are the significant factors influencing the perceived service quality services of the local government. Among them, responsiveness was found to the most significant followed by logistic support, empathy, reliability and tangibles. The outcome of this research work has enriched the existing body of knowledge in the field of local government’s service quality. The policy makers, local government and other related stakeholders might find this study as an essential tool in designing, developing and implementing their activities directed to the slum dwellers.